3n-2m=mn+4

Simple and best practice solution for 3n-2m=mn+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3n-2m=mn+4 equation:


Simplifying
3n + -2m = mn + 4

Reorder the terms:
-2m + 3n = mn + 4

Reorder the terms:
-2m + 3n = 4 + mn

Solving
-2m + 3n = 4 + mn

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1mn' to each side of the equation.
-2m + -1mn + 3n = 4 + mn + -1mn

Combine like terms: mn + -1mn = 0
-2m + -1mn + 3n = 4 + 0
-2m + -1mn + 3n = 4

Add '-3n' to each side of the equation.
-2m + -1mn + 3n + -3n = 4 + -3n

Combine like terms: 3n + -3n = 0
-2m + -1mn + 0 = 4 + -3n
-2m + -1mn = 4 + -3n

Reorder the terms:
-4 + -2m + -1mn + 3n = 4 + -3n + -4 + 3n

Reorder the terms:
-4 + -2m + -1mn + 3n = 4 + -4 + -3n + 3n

Combine like terms: 4 + -4 = 0
-4 + -2m + -1mn + 3n = 0 + -3n + 3n
-4 + -2m + -1mn + 3n = -3n + 3n

Combine like terms: -3n + 3n = 0
-4 + -2m + -1mn + 3n = 0

The solution to this equation could not be determined.

See similar equations:

| X+7x=-24 | | 5y^2+40y=325 | | 5(3x-7)-3(x+2)-19x= | | 3(x-2)+(-3)=4(x+1) | | r(2x+3)=0.5x+1 | | b^2=-2+3b | | 20x+12y=344 | | 2(5z-1)-5(z+9)=2(z+1) | | 18-3x=2+2x | | 9n^2=-1 | | 5(3/2)+3(4/2)= | | 41+a=10 | | 2xy-3y+6=0 | | 3x-5=24+7 | | (3x-18)=105+99 | | 5.4+-9.7= | | 2/3x-1/2=3/4 | | 29n=-377 | | 2(x+3)=4*-3 | | (2x-4)2=36 | | 4(6x-31)=5-4(x+3) | | 7(4x+8)-6=-106 | | 3v^2+12v=-8 | | 7x-4=-2x+2+9x-5 | | 9(x+1)=25+6 | | -2(2-x)=-8+6x | | 11+2n=9 | | -7(1x-6)=-14 | | 57=5x-3 | | -3(5m+4)-3(m-7)= | | y-12=89 | | 5x^2+11xy+2y^2=0 |

Equations solver categories